Heat shock proteins in hypothermia: a review - Song, Shang-Jin; Wu, Guo-Cheng; Yi, Li; Liu, Xin; Jiang, Ming-Min; Zhang, Xiao-Chen; Yin, Zi-Fei; Gu, Wei; Ruan, Yi (Frontiers in Molecular Biosciences, 2025)
Hypothermia is a serious condition marked by a significant decrease in core body temperature, posing considerable risks to biological systems. In response to thermal stress, cells activate protective mechanisms, often synthesizing heat shock proteins (HSPs). These highly conserved proteins are crucial in cellular stress responses, primarily functioning as chaperones. HSPs facilitate correct protein folding and prevent misfolding and aggregation, thereby protecting cellular integrity during adverse conditions. This paper explains how HSPs alleviate stress responses related to low body temperature, focusing on energy metabolism, apoptosis, cellular membrane fluidity and stability, and stress signaling pathways. By enhancing cellular repair mechanisms, HSPs help maintain cellular balance and prevent further harm to the organism. Ultimately, the review emphasizes the complex relationship between cellular stress responses and HSPs in hypothermia, highlighting their potential as therapeutic targets for enhancing resistance to the harmful effects of extreme cold exposure. A deeper understanding of these mechanisms could lead to strategies that improve survival rates in hypothermic patients. It may also reveal ways to modulate HSPs’ activity for enhanced cellular protection.